The Columbia guide to East African literature in English since 1945 - Gikandi, Simon (Columbia guides to literature since 1945., 2007)
The Columbia Guide to East African Literature in English Since 1945 challenges the conventional belief that the English-language literary traditions of East Africa are restricted to the former British colonies of Kenya, Uganda, and Tanzania. Instead, these traditions stretch far into such neighboring countries as Somalia and Ethiopia. Simon Gikandi and Evan Mwangi assemble a truly inclusive list of major writers and trends. They begin with a chronology of key historical events and an overview of the emergence and transformation of literary culture in the region. Then they.